2015
DOI: 10.3390/aerospace2020353
|View full text |Cite
|
Sign up to set email alerts
|

Shock Wave Attenuation Using Foam Obstacles: Does Geometry Matter?

Abstract: A shock wave impact study on open and closed cell foam obstacles was completed to assess attenuation effects with respect to different front face geometries of the foam obstacles. Five different types of geometries were investigated, while keeping the mass of the foam obstacle constant. The front face, i.e., the side where the incident shock wave impacts, were cut in geometries with one, two, three or four convergent shapes, and the results were compared to a foam block with a flat front face. Results were obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…While much prior work has studied how to engineer lattice materials for enhanced energy absorption properties, most applications primarily use stochastic foams to achieve these functions, which, due to their random structure, are not optimized and are difficult to simulate. Individual works have studied the benefits of engineered periodic structures compared to those of random foams in 2D . However, a comprehensive comparison of energy absorbing properties from periodic to stochastic structures in 3D cellular materials remains missing.…”
Section: Introductionmentioning
confidence: 99%
“…While much prior work has studied how to engineer lattice materials for enhanced energy absorption properties, most applications primarily use stochastic foams to achieve these functions, which, due to their random structure, are not optimized and are difficult to simulate. Individual works have studied the benefits of engineered periodic structures compared to those of random foams in 2D . However, a comprehensive comparison of energy absorbing properties from periodic to stochastic structures in 3D cellular materials remains missing.…”
Section: Introductionmentioning
confidence: 99%
“…The top spiral is just the reflection of the bottom spiral. The performance of this geometry has been assessed with numerous experiments and simulations (Milton 1989, Inoue et al 1993, 1995, Jeon et al 2015, Wan and Eliasson 2015, showing in all cases that a section reduction based on logarithmic spirals is effective at focusing the incoming wave. With this in mind, we can hypothesize that a geometry like this could potentially be used as the driver of an explosively driven blast facility.…”
Section: Basic Conceptmentioning
confidence: 99%
“…In this regard, a comprehensive review of various methods to attenuate shock/blast waves was reported by Igra et al [ 2 ] addressing both experimental and numerical approaches. Essentially, shock-wave attenuation by geometrical means such as rigid barriers or sudden changes in the flow geometries is governed by compression, rarefaction regions arising from shock diffraction and intense shock-turbulence interactions [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. These involve multiple wave interactions, reflecting from surrounding boundaries and complex shock-shock, shock-vortex and shock-boundary layer interactions.…”
Section: Introductionmentioning
confidence: 99%